Prospective, multicenter study of 2-level cervical arthroplasty with a PEEK-on-ceramic artificial disc - Coric, Domagoj; Guyer, Richard D; Bae, Hyun; Nunley, Pierce D; Strenge, K Brandon; Peloza, John H; Boltes, Margaret O; Ohnmeiss, Donna D (Journal of neurosurgery. Spine, 2022)
The purpose of this study was to evaluate the safety and efficacy of a PEEK-on-ceramic cervical total disc replacement (cTDR) device for the treatment of 2-level cervical disc disease with radiculopathy and/or myelopathy. The study was a prospective, nonrandomized, historically controlled FDA investigational device exemption trial evaluating the Simplify Cervical Artificial Disc for use at 2 levels. The anterior cervical discectomy and fusion (ACDF) control group was derived from a propensity score-matched (using subclassification) cohort of patients who participated in an earlier prospective trial in which similar indications were used. The follow-up duration was 24 months. The primary outcome was a 4-point composite success classification. Other validated clinical and radiographic assessments were also evaluated. The investigational group (n = 182) was compared with patients who underwent ACDF (n = 170) in a historical control group using propensity score analysis. The overall composite success rate was statistically significantly greater in the cTDR group compared with the ACDF group (86.7% vs 77.1%; p < 0.05). The mean Neck Disability Index scores improved significantly in both groups, with cTDR significantly lower at some follow-up points. At the 24-month follow-up, a minimum 15-point improvement in Neck Disability Index scores was achieved in 92.9% of the cTDR group and 83.5% of the ACDF group (p > 0.05). In both groups, neck and arm pain scores improved significantly (p < 0.05) by 6 weeks and improvement was maintained throughout follow-up. Segmental range of motion was maintained at both treated segments in the cTDR group. MRI performed in the cTDR group at 24 months postoperatively found minimal changes in facet joint degeneration. The rate of subsequent surgical intervention was 2.2% in the cTDR group and 8.8% in the ACDF group. This study adds to the growing body of literature supporting cTDR for 2-level cervical disc disease with radiculopathy or myelopathy. cTDR showed a superior overall success rate compared to ACDF, while maintaining motion. These results support that the Simplify disc is a viable alternative to ACDF in appropriately selected patients with 2-level cervical spondylosis.